Substrate topography regulating membrane adhesion mediated by receptor-ligand bonds - Ma, Yuanyuan; Li, Long; Smith, Ana-Suncana (Applied Physics Letters, 2024)
Cell adhesion can be significantly influenced by the topography of the substrate surface. However, how the adhesion molecules essentially respond to this topographical stimulus is not fully understood yet. Here, we employ an effective Monte Carlo simulation to systematically investigate a fluctuating membrane interacting with a curved substrate via adhesive proteins. Interestingly, results show that, compared with the flat substrate, curved substrates regulate the membrane adhesion in a bond length dependent manner. The effects of the substrate surface amplitude and wavelength on the number of molecular bonds and adhesion pattern are also extracted from the scaling relationship between the characteristic lateral length of the membrane and the local substrate curvature radius. Furthermore, the local substrate curvature is found to select the bond distribution in terms of the bond length and stiffness. The results suggest that the bond stiffness enhances the clustering of molecular bonds, mainly due to synergistic interactions among these molecular bonds.
CRIS-Team Scopus Importer:2024-10-25